Perfil sorológico anti-Brucella abortus em bezerras vacinadas com amostras B19 - Ribeiro, Márcio Garcia [UNESP]; Spago, N.; Fava, N.; Ratti, J.; Megid, Jane [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 1997)
The serological profiles of 33 female bovines, vaccinated at three to eight months of age with the B19 standard strain of Brucella abortus, were studied over a period of 728 days, using the following agglutination procedures: plate agglutination, tube agglutination, rose bengal plate and mercaptoethanol test. Maximum levels of antibodies detected reached by the plate agglutination and tube agglutination tests were found between the 14(th) and 42(nd) day, and with mercaptoethanol test, between the 28(th) and 42(nd) day. Anti-Brucella antibodies decreased thereafter. At 182 days after vaccination, five suspected animals and one positive were detected by the plate agglutination test, while by the tube agglutination test, only one animal was suspected and another one was positive. During the same period, positive reactions were found in six animals by means of the mercaptoethanol test, and five positives by the rose bengal test. By means of tube agglutination and plate agglutination tests, the animals became serologically negative at 245 and 273 days, respectively, after the vaccination, based on the rules adopted for the vaccinated animals. Using the mercaptoethanol and rose bengal plate tests, all the animals were found to be negative at 308 days after vaccination.
Serological response of vaccinated female calves against Brucella abortus
Keywords: Brucellosis; agglutination test; B19; bovine